Oxidative stress and DNA damage status in couples undergoing in vitro fertilization treatment. Issue 2 (18th May 2021) - Al-Saleh, Iman; Coskun, Serdar; Al-Rouqi, Reem; Al-Rajudi, Tahreer; Eltabache, Chafica; Abduljabbar, Mai; Al-Hassan, Saad
Abstract : This study examined the status of oxidative stress in 599 couples undertaking in vitro fertilization (IVF) treatment and its association with reproductive hormones, smoking, and outcomes. Oxidative stress biomarkers such as malondialdehyde, 8-hydroxy-2-deoxyguanosine, hydrogen peroxide (H2 O2 ), catalase (CAT), and total antioxidant capacity (TAC) were determined in follicular fluid and seminal plasma. Tail moment (TM) was used to evaluate DNA damage in the sperm and granulosa cells. Reproductive hormones in serum and cotinine (COT) in urine, follicular fluid, and seminal plasma samples were determined. Separate multivariate linear regression was used to assess associations between levels of each oxidative stress biomarker and each hormone and smoking parameter (modeled as natural log-transformed). The findings indicate that some oxidative stress and DNA damage biomarkers played a role in disrupting certain reproductive hormones in women and their male partners either by overproducing reactive oxygen species or reducing antioxidant defense capacity. Although women were nonsmokers, COT levels > 50 and 10 µg/L in urine and follicular were observed in 5.7 and 1.7%, respectively. Levels of follicular fluid COT were positively associated with H2 O2 and TM. We used log-binomial multivariate regression to estimate relative risks for the association between oxidative stress/DNA damage and IVF binary outcomes (fertilization rate > 50%, biochemical pregnancy, clinical pregnancy, and live birth). An increase in the CAT levels of follicular fluid was associated with a 48 and 41% decrease in the risk of poor fertilization rate (≤50%) and unsuccessful live birth, respectively. After the models were adjusted for hormonal factors, the associations remained the same, except that the elevated TAC in follicular fluid became significantly associated with a decrease of 42% in the risk of poor fertilization rate (≤50%). The higher antioxidant activity (CAT and TAC) in follicular fluid might positively impact specific IVF outcomes. Lay summary: Oxidative stress occurs when antioxidant molecules are insufficient in the body to destroy free radicals that can damage the cells, proteins and DNA, causing different health conditions, including infertility. The role of oxidative stress in female infertility has not received as much attention as male infertility, and research is still limited. This study explored whether the overproduction of free radicals can impact the success of in vitro fertilization (IVF) treatment using several biological markers such as hydrogen peroxide, catalase, and total antioxidant capacity. Our findings revealed that the high antioxidant levels in the fluid surrounding the egg were linked with a high fertilization rate. Additionally, oxidative stress status in couples was associated negatively with several reproductive hormones and smoking status. Biomarkers of oxidative stress and DNA damage might have potential applications in evaluating IVF patients' clinical characteristics such as causes of infertility, hormonal profile, fertilization rate, implantation and live birth.